The Penderwicks at Point Mouette [compact disc, unabridged] - Birdsall, Jeanne (Birdsall, Jeanne. Penderwicks series, 2011)
When summer comes around, it's off to the beach for Rosalind ... and off to Maine with Aunt Claire for the rest of the Penderwick girls, as well as their old friend, Jeffrey. That leaves Skye as OAP (oldest available Penderwick)--a terrifying notion for all, but for Skye especially.